The Equity Premium Puzzle and Duration of Equities and Bonds in South Africa - KHOZA, SITHEMBISO (My University, 2011)
Historical research has found a larger than expected premium between equity returns and bond returns. This large premium in observed returns is much larger than the expected premium derived from risk/return equilibrium pricing models. Despite innumerable attempts to explain this anomaly, no satisfactory solution or answer has been found. This research looked at equity and bond returns in South Africa to establish if a similar anomaly exists. It was found that there is a premium of 2.4 % when comparing equity returns to t-bill returns. Financial markets data was collected from I-Net Bridge and premiums were calculated for different maturity bonds in order to isolate the impact of duration on the risk premium. Long bonds which have longer duration than t-bills were found not offer such a large equity premium. It was found that a large part of the equity premium can be explained by the differences in duration. The conclusion is that when calculating the risk premium, there should be a clear separation between risk premium and term premium. Moving from the understanding that the equity premium is comprised of two components, the risk premium and the term premium, this research found that a large part of the equity premium comes from the term premium.
MBA - WBS
Keywords: Equities; Bonds